Estrategias de marketing digital para el posicionamiento del Centro Recreativo Mirador Yagüi urco del cantón san Miguel de Bolívar, año 2022 - Moposita Saltos, Erika Karolina (2022)
This research work was carried out with the need to create digital marketing strategies to help the positioning of the Yagüi Urco recreational center in the canton of San Miguel de Bolivar, using appropriate digital tools for the proper creation of strategies, the recreational center began its tourist exploitation in July 2021 which has failed to be recognized and positioned. For the positioning of the site we have worked in four main and important chapters for the continuity of the research, chapter I, begins with a general analysis of the current situation that is to say the problems of the site, followed by what is going to be done to solve the problem, continues with the objectives that we want to achieve, chapter II focuses on the theoretical framework, that is to say the laws and theoretical bases that are extremely important concepts, chapter III refers to the methodology used as the bibliographic research, field research and descriptive research, techniques and instruments such as survey, interview and observation are very important tools to obtain accurate and important information for the creation of strategies, followed by chapter IV based on the results and discussion, this chapter is important because it helps the implementation of digital strategies in this way help the place to have a better and better positioning in the market by solving the research problems. With the proposal put forward on the creation of digital marketing strategies, the Yagui Urco recreational center mirador, wants to grow competitively and thus achieve positioning and greater market share. It ends with the conclusions, recommendations and annexes that confirm and support the research and information obtained. Keywords: Digital marketing, Positioning, Market, Digital tools, Branding.